IMPLEMENTASI ALGORITMA BRUTE FORCE PADA PENCARIAN DATA KEPEMILIKAN TANAH - Reza Risky Khamdani; Indah Puji Astuti; Fauzan Masykur (Universitas Muhammadiyah Ponorogo, 2021)
Geographical information system is a system that combines elements on a map that is prepared to process data, analyze, and display spatial data to improve design. In the era of technology, information and communication (ICT) for organizations, agencies and public services is very important and needs to be implemented immediately. ATR / BPN in Jonggol village, Jabon, Ponorogo, still uses the manual method in processing certified land registration. The process of seeking, processing, and collecting certificate data requires a lot of time, causing services to be inefficient and effective and community satisfaction also decreasing. Therefore, a technology is needed that can facilitate service officers to search for certified land ownership data by implementing the brute force algorithm in the Geographical Information System for certified land ownership. The application of Algortima Brute Force in this geographic information system can run well, but if the text characters are long inputted, the system search process will take longer (if the text is short, the search can run quickly). On 10 keywords with different keyword or character lengths, the average search time was 0.06335 seconds.